Neonatal Outcome and Mode of Delivery with Nuchal Cord - A Cross Sectional Study - Uzma Manzoor, Nadia Sharif, Sadaqat Ali, Mumtaz Jehan, Mohammad Zain, Musa Salman, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the incidence of umbilical cord around the fetal neck and its effects on fetal outcome. Study Design: It is single center cross sectional study. Duration: The duration of study is two year from January 2020 to January 2021. Settings: This study was carried out in Independent University Hospital Faisalabad. Methodology: All patients presents after 28 weeks upto 41 weeks of gestation either delivered by caesarean section or delivered vaginal birth with baby having one, two or three loops of cord around the neck were selected. Fetal outcome was observed, maternal age, Parity, Gestational age, Mode of delivery, APGAR score and admission to NICU were noted. Results: A total of 102 patients (27.4%) were delivered having nuchal cord 65 patients (63.7%) were in age group (26-30y) and 60 patients (58%) were multipara delivered with cord around the neck of fetus. In present study cesarean section rate was 70.5%. In 25 patients (24.5%) nuchal cord was diagnosed before delivery and in 77 patients (75.4%) nuchal cord was incidental findings during labour. Regarding fetal outcome; In 47 babies (46%) delivered with nuchal cord were having APGAR score less than 5 but in 55 babies (53.9%) having good APGAR score. Conclusion: Nuchal cord is common incidental finding during labour and fetal outcome regarding APGAR score & NICU admission was better in patients delivered with nuchal cord. But the cesarean section rate was higher. Keywords: Nuchal cord, Frequency, Fetal outcome